2017
DOI: 10.1002/2017gl075003
|View full text |Cite
|
Sign up to set email alerts
|

Why Flash Type Matters: A Statistical Analysis

Abstract: While the majority of research only differentiates between intracloud (IC) and cloud‐to‐ground (CG) flashes, there exists a third flash type, known as hybrid flashes. These flashes have extensive IC components as well as return strokes to ground but are misclassified as CG flashes in current flash type analyses due to the presence of a return stroke. In an effort to show that IC, CG, and hybrid flashes should be separately classified, the two‐sample Kolmogorov‐Smirnov (KS) test was applied to the flash sizes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Further, only flashes that initiated within 100 km from the center of NALMA were used in the analysis, while all VHF sources related to each flash were included, even if the VHF source was located outside of the 100‐km range, leading to a 200 × 200‐km domain for our analysis (refer to Figure S1 in the supporting information for a map of the area of interest). The flash sizes were obtained by using the square root of the convex hull (or polygon) area surrounding the VHF sources in the horizontal, as in Bruning and MacGorman (), Mecikalski and Carey (), Mecikalski et al (), and Mecikalski et al ().…”
Section: Data Storm Type Classification and Methodologymentioning
confidence: 99%
“…Further, only flashes that initiated within 100 km from the center of NALMA were used in the analysis, while all VHF sources related to each flash were included, even if the VHF source was located outside of the 100‐km range, leading to a 200 × 200‐km domain for our analysis (refer to Figure S1 in the supporting information for a map of the area of interest). The flash sizes were obtained by using the square root of the convex hull (or polygon) area surrounding the VHF sources in the horizontal, as in Bruning and MacGorman (), Mecikalski and Carey (), Mecikalski et al (), and Mecikalski et al ().…”
Section: Data Storm Type Classification and Methodologymentioning
confidence: 99%
“…However, early assessment studies have shown that the GLMs have a higher detection efficiency for CG flashes than IC flashes (Bitzer, 2019; Yoshida, 2019). The so‐called hybrid flashes with extensive IC components as well as connections to ground complicate this interpretation and may sometimes be as common as CG flashes that exclusively have channels in the lower part of the cloud (Mecikalski et al, 2017; Mecikalski & Carey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Carey et al () suggests that total flash rate may be well correlated to storm intensity, while flash extent (FE) might not be at times. Several studies have investigated changes in FCL profiles, but sensitivity of final LNO x concentration to initial placement remains unclear (e.g., Fehr et al, ; Fuchs & Rutledge, ; Hansen et al, ; Labrador et al, ; Mecikalski et al, ; Ott et al, , ; Pickering et al, ). For example, Hansen et al () found the vertical structure of flashes to vary, with more intense thunderstorms having a bimodal FE distribution compared to the predominant unimodal distribution seen in less intense thunderstorms, suggesting a correlation in vertical charge structure to storm intensity.…”
Section: Introductionmentioning
confidence: 99%